1995
DOI: 10.1182/blood.v85.11.3028.bloodjournal85113028
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the cysteine-rich domain of glycoprotein IIIa in the expression of the human platelet alloantigen, PlA1: evidence for heterogeneity in the humoral response

Abstract: To assess the potential contribution of the cysteine-rich domain of human platelet glycoprotein (GP) IIIa to the structure of the PlA1 epitope, we used site-directed mutagenesis to substitute alanines for cysteines at key positions potentially involved in PlA1 alloantigen formation. One of these GPIIIa isoforms in which alanine replaced Cys435 reacted normally with a series of well-characterized murine MoAbs directed against the 250 amino-terminal residues of GPIIIa, whereas binding of MoAbs specific for resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…T cell clones had dissimilar TCR genes [20,21] that could affect their affinity for peptides. Anti-HPA-1a antibodies are known to be heterogeneous for their epitope specificity [80] and functional activity [81], and the large range in anti-HPA-1a concentrations we found (Table 1) may reflect differences in IgG affinity maturation. Importantly, unpredictable fluctuations in circulating HPA-1aspecific T cells occur in both pregnant [18] and nonpregnant FNAIT women (Table 3).…”
Section: Discussionmentioning
confidence: 89%
“…T cell clones had dissimilar TCR genes [20,21] that could affect their affinity for peptides. Anti-HPA-1a antibodies are known to be heterogeneous for their epitope specificity [80] and functional activity [81], and the large range in anti-HPA-1a concentrations we found (Table 1) may reflect differences in IgG affinity maturation. Importantly, unpredictable fluctuations in circulating HPA-1aspecific T cells occur in both pregnant [18] and nonpregnant FNAIT women (Table 3).…”
Section: Discussionmentioning
confidence: 89%
“…6 As well, studies have shown that different alloantibodies against HPA-1a recognize different epitopes on GPIIIa. 21 Therefore, it is possible that alloantibodies against some epitopes are inherently more pathogenic and lead to more severe clinical presentation. 22 The syndrome of thrombocytopenia due to passive transfer of PLT antibody is self-limited, and patients with asymptomatic thrombocytopenia do not require treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The HUVEC model, however, is an artificial model and vascular damage in vivo might occur after more prolonged exposure to antibodies or by a more complex interaction in the presence of accessory factors, provided by granulocytes, monocytes, proinflammatory mediators, platelets and pro-coagulants. Cerebral vascular endothelium may differ from HUVEC, because periventricular vessels have been demonstrated to have a high expression of Fc-IgG receptors [51] and because heterogeneity of HPA-1a expression in different cerebral vessels [4] could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…First, the titre, IgG-subclass, or ability to activate complement of HPA-antibodies might be involved [9,10,16] or the co-existence of HLA antibodies, which enhance immune-mediated damage induced by HPA-antibodies [9,[17][18][19]. Secondly, differences in the GPIIIa-domains recognized by anti-HPA-antibodies might influence the manifestation of the disease [4] and thirdly, as the GPIIb/IIIa-complex is expressed on ECs, binding of anti-HPA antibodies to HPAantigen on the endothelial surface might induce vascular tissue damage [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%